Design, synthesis and evaluation of novel β-carboline ester analogues as potential anti-leishmanial agents. Issue 23 (19th December 2022) - Karan Kumar, Banoth; Faheem,; Balana Fouce, Rafael; Melcon-Fernandez, Estela; Perez-Pertejo Yolanda, Yolanda; Reguera, Rosa M.; Adinarayana, Nandikolla; Chandra Sekhar, Kondapalli Venkata Gowri; Vanaparthi, Satheeshvarma; Murugesan, Sankaranarayan
Abstract: Leishmaniasis is one of today's most neglected diseases. The emergence of new anti-leishmanial therapies emphasizes several study groups funded by the World Health Organization. The present investigation will focus on the research to determine a few new potential derivatives of β-carboline ester derivatives against leishmaniasis. The in-silico predicted ADMET properties of most of the titled compounds are in an acceptable range and having drug like properties. Among all the tested analogs, compound ES-3 (EC50 3.36 μM; SI > 29.80) showed comparable and equipotent anti-leishmanial activity as that of standard drug miltefosine (EC50 4.80 μM; SI > 20.80) against amastigote forms of the tested L. infantum strain. Two compounds ES-6 and ES-10 exhibited significant activity with EC50 10.16, 13.56 μM; SI > 4.90, 7.37, respectively. In-silico based molecular docking and dynamics study of the significantly active analog also performed to study the putative binding mode, interaction pattern at the active site of the target leishmanial trypanothione reductase enzyme as well as stability of the target-ligand complex. The changes in the conformation of molecules during MD (frame wise trajectory analysis) provided new insights for the development of novel potent molecules. These findings will further give insight that will help modify the compound ES-3 for better potency and the design of novel inhibitors for leishmaniasis. Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001